Mortar Materials

JP7637287B1Active Publication Date: 2025-02-27DENKA CO LTD
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2024056230
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-03-29
Publication Date
2025-02-27
Estimated Expiration
2044-03-29

AI Technical Summary

Benefits of technology

【0008】 本発明によれば、流動性が良好で、優れた充填性を有するモルタル材料を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007637287000001
    Figure 0007637287000001
  • Figure 0007637287000002
    Figure 0007637287000002
  • Figure 0007637287000003
    Figure 0007637287000003
Patent Text Reader

Abstract

The object of the present invention is to provide a mortar material having good fluidity and excellent filling properties. The vibration viscosity of mortar immediately after mixing with a standard water ratio, as measured with a vibration viscometer, is 50 to 600 (mPa·s·g / cm 3 The fine aggregate contained therein has a coarse grain ratio of preferably 1.2 or more and 2.2 or less, and the ratio of the mass of the fine aggregate to the total mass of the cement and the expansive material is preferably 60 to 230%.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a mortar material. [Background technology]

[0002] Concrete used in the construction of buildings or civil engineering structures contains cement, water, aggregate, etc., and has the property of hardening through the hydration reaction of cement. After hardening, concrete may crack due to volume changes caused by the action of stress, temperature changes, drying, etc. Cracks in concrete can cause water leakage, rebar corrosion, etc., and are a major factor in significantly reducing durability, so if the cracks are severe, they must be repaired. For example, cracks that occur in concrete structures such as tunnels and bridges are repaired by injecting mortar or repairing the cross section.

[0003] For example, the following Patent Document 1 describes such a mortar as being excellent in resistance to material separation, fluidity, and usable life, by using a thickener having a specific viscosity and adjusting the content of a shrinkage-reducing agent and a pozzolanic substance. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2021-130570 A Summary of the Invention [Problem to be solved by the invention]

[0005] When repairing concrete structures, it is desirable to set the fluidity of the mortar within a desired range in order to prevent dripping when mortar is injected into cracks or applied to a wall surface. Patent Document 1 describes the use of a thickener having a predetermined range of viscosity, but does not describe the viscosity of the mortar itself. In addition, the viscosity of the thickener was measured using a rotational viscometer, and since the thickener is actually used in places where repairs are often performed on bridges and other structures that are subject to a lot of vibration, there was a need to measure the viscosity in accordance with actual use.

[0006] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a mortar material having good fluidity and excellent filling properties. [Means for solving the problem]

[0007] As a result of intensive research into solving the above problems, the present inventors have found that the above problems can be solved by setting the vibration viscosity measured by a vibration viscometer to a predetermined range, and have arrived at the present invention. [1] The vibration viscosity of mortar immediately after mixing with a standard water ratio is 50 to 600 (mPa s g / cm) measured with a vibration viscometer. 3 ) is a mortar material. [2] The mortar material according to [1], which contains fine aggregate, and the fine aggregate has a coarse particle ratio of 1.2 to 2.2. [3] The mortar material according to [1] or [2], containing cement, an expansive material, and a fine aggregate, wherein the ratio of the mass of the fine aggregate to the mass of the binder including the cement and the expansive material is 60 to 230%. [4] The fine powder that passed through a 90 μm sieve was found to have the following chemical components: TiO 2 The mortar material according to any one of [1] to [3], containing 0.03 mass % or more of the following. [5] The fine powder that passed through a 90 μm sieve was found to have the following chemical components: 2 O 5 The mortar material according to any one of [1] to [4], containing 0.05 to 5 mass % of the above. [6] The mortar material according to any one of [1] to [5], which contains a foaming substance. Effect of the Invention

[0008] According to the present invention, it is possible to provide a mortar material having good fluidity and excellent filling properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The mortar material of the present invention will be described in detail below, but the present invention is not limited to this embodiment. In this specification, "%" and "parts" are based on mass unless otherwise specified. In addition, a numerical range specified using the symbol "~" includes the numerical values ​​at both ends (upper and lower limits) of "~".

[0010] [Mortar materials] The mortar material of this embodiment has a vibration viscosity of 50 to 600 (mPa·s·g / cm) measured by a vibration viscometer immediately after mixing with a standard water ratio. 3 The vibration viscosity is 80 to 500 (mPa·s·g / cm 3 ), and 100 to 400 (mPa·s·g / cm 3 ) is more preferable. The vibration viscosity is 50 (mPa·s·g / cm 3 ), dripping occurs easily when the mortar is applied to the wall, and workability such as trowel finishing decreases. 3 ), it becomes difficult to inject mortar deep into the crack to be repaired, and the filling ability of the mortar decreases.

[0011] The vibration viscosity can be adjusted to the above range by, for example, adding a thickener as described later. Also, the particle size of the fine aggregate as described later can be adjusted. By making the particle size finer, the vibration viscosity can be lowered, and by making the particle size coarser, the vibration viscosity can be increased.

[0012] Incidentally, mixing at a standard water ratio means adding 15 to 21 parts by mass of water to 100 parts by mass of the mortar material and mixing the mixture. The vibration viscosity value is the value measured for this mortar. "Immediately after mixing" means that the measurement is started within 5 minutes after the completion of mixing, and the vibration viscosity measured is the vibration viscosity 1 minute after the start of the measurement.

[0013] A vibration viscometer measures the viscosity of a liquid by inserting a vibrator into the mortar to be measured and detecting the force required for vibration when the vibrator is vibrated under a constant displacement condition. The vibration viscometer measures vibrational viscosity, which is the product of viscosity and density. Since vibration viscosity is measured while vibrating the mortar, it is possible to suppress settling and separation of the mortar during measurement, and therefore it is possible to measure the viscosity with a more accurate value. Also, compared to a rotational viscometer, it is possible to suppress the temperature rise of the mortar due to frictional heat, so it is possible to measure the viscosity without considering temperature changes due to the measurement method. Furthermore, since it can be measured with simple operations, it is possible to measure on-site, and it is possible to measure the vibration viscosity of mortar that is actually used.

[0014] The instrument used to measure the vibration viscosity is not particularly limited, but for example, a tuning fork vibration viscometer SV-10 (manufactured by A&D Co., Ltd.) can be used.

[0015] The mortar material of this embodiment has a vibration viscosity measured with a vibration viscometer within the above-mentioned range, so that when made into mortar, it has good fluidity and excellent filling properties that enable the mortar to be filled deep into cracks, etc. that are to be repaired.

[0016] (Composition of mortar materials) Next, the composition of the mortar material of the present embodiment will be described. The mortar material of the present embodiment preferably contains cement, an expansive material, and a fine aggregate.

[0017] [cement] The cement used in this embodiment is not particularly limited, and examples thereof include various cements such as normal, early strength, super early strength, low heat, and medium heat, various mixed cements obtained by mixing these cements with blast furnace slag, fly ash, silica fume, etc., environmentally friendly cements (ecocement) manufactured using municipal waste incineration ash and sewage sludge incineration ash as raw materials, commercially available fine particle cements, etc., and various cements and various mixed cements can be used in a fine powder form. Also, cements adjusted by increasing or decreasing the amount of components (e.g., gypsum) used in normal cements can be used. In this embodiment, it is preferable to select ordinary Portland cement or high-early-strength Portland cement from the viewpoints of heat of hydration, drying shrinkage, and filling properties.

[0018] In addition, as described below, the fine powder that passed through a sieve with a mesh size of 90 μm contained TiO as a chemical component. 2 , P 2 O 5 In the case of containing, for example, CaO raw material, SiO 2 Raw material, Al 2 O 3 Raw materials and Fe 2 O 3 Raw materials and, if necessary, TiO 2 Raw material, P 2 O 5 Cement can be produced by mixing the raw materials, calcining them to synthesize clinker, and pulverizing them using a ball mill. At this time, the CaO content is preferably 10 to 70 mass%, and Al 2 O 3 is preferably 1 to 20 mass %, and Fe 2 O 3 is preferably 0.1 to 40 mass %.

[0019] The CaO raw material is, for example, calcium oxide powder, limestone powder, Al 2 O 3 The raw materials are, for example, aluminum oxide powder, bauxite powder, Fe 2 O 3 The raw material is, for example, iron oxide powder, SiO 2The raw materials are, for example, silicon dioxide powder, silica powder, TiO 2 The raw material is, for example, titanium oxide powder, P 2 O 5 The raw material may be, for example, calcium phosphate powder.

[0020] The cement used in this embodiment has a Blaine specific surface area of ​​2,500 cm from the viewpoint of production cost and strength development. 2 / g or more 7,000cm 2 / g or less, and 2 / g or more 6,000cm 2 / g or less is more preferable, and 2 / g or more 4,500cm 2 It is more preferable that the molecular weight is not more than 1 / g. The Blaine specific surface area value is determined in accordance with JIS R 5201 (physical testing method for cement).

[0021] [Expansion material] The expanding material used in this embodiment is not particularly limited, and any material that can generate an expansive hydrate and suppress bleeding can be used. Known expansive materials include free lime, free magnesia, calcium ferrite, ettringite, lime, and ettringite-lime composites, and are not particularly limited, but from the viewpoint of long-term stability, those containing free lime are preferred. Examples of those containing free lime include free lime-anhydrous gypsum, free lime-hydraulic compound, and free lime-hydraulic compound-anhydrous gypsum.

[0022] In this embodiment, it is preferable to use a free lime-hydraulic compound-anhydrous gypsum system because of its good expansion performance, and it is particularly preferable to use one having a free lime content of more than 40 mass %. Here, the hydraulic compound may be, for example, one or more of auin, calcium ferrite, calcium aluminoferrite, calcium silicate, calcium aluminate, etc. In this embodiment, the expansive material may be a commercially available expansive material or a static crushing material. Expansion agents and static crushing agents are commercially available from various companies. Representative examples include Denka CSA#20 and Denka Power CSA manufactured by Denka Co., Ltd., and Expan, Hyper Expan, N-EX, and Blaster manufactured by Pacific Materials Corporation, as well as crushed products of these.

[0023] The particle size of the expanding material used in this embodiment is not particularly limited, but is preferably 2,000 cm in terms of Blaine specific surface area. 2 / g or more 25,000cm 2 / g or less is preferable, and 2,200 cm 2 / g or more 15,000cm 2 / g or less is preferable, and 2,400 cm 2 / g or more 10,000cm 2 / g or less is more preferable. By setting the Blaine specific surface area of ​​the expanding material to the above lower limit or more, bleeding can be suppressed. Also, by setting the Blaine specific surface area of ​​the expanding material to the above upper limit or less, sufficient expandability can be obtained.

[0024] The content of the expansive material used in this embodiment is preferably 0.5 parts by mass or more and 20 parts by mass or less, more preferably 1 part by mass or more and 18 parts by mass or less, and even more preferably 2 parts by mass or more and 15 parts by mass or less, relative to 100 parts by mass of cement. When the content of the expansive material is equal to or more than the lower limit, it becomes easier to obtain a crack suppression effect. On the other hand, when the content of the expansive material is equal to or less than the upper limit, strength expression becomes good. When the content of the expansive material is within the above range, it becomes easy to obtain a mortar with excellent drying shrinkage and filling properties.

[0025] [Fine aggregate] The fine aggregate used in this embodiment may be any commonly used fine aggregate, such as river sand, mountain sand, crushed sand, lime sand, silica sand, colored sand, sea sand, or a combination of these.

[0026] The fine aggregate has a coarse particle ratio of preferably 1.2 to 2.2, more preferably 1.2 to 2.1, and even more preferably 1.3 to 2.0. By setting the coarse particle ratio of the fine aggregate within the above range, excellent fluidity can be obtained. The coarse aggregate ratio can be calculated based on JIS A 1102:2014 "Sieving test method for aggregates".

[0027] Furthermore, the ratio of the mass of the fine aggregate to the mass of the binder containing cement and expansive agent is preferably 60 to 230%, more preferably 80 to 220%, and even more preferably 90 to 210%. By setting the ratio of the fine aggregate in the above range, the effect of retaining fluidity and the ability to apply thickly can be improved.

[0028] [Thickener] The mortar material of the present embodiment may contain a thickener. The vibration viscosity of the mortar can be adjusted by the thickener. Examples of the thickener include water-soluble polymeric substances such as methyl cellulose (MC), carboxymethyl cellulose (CMC), polyvinyl alcohol (PVA), polyacrylamide, and polyethylene oxide (PEO). In order to keep the vibration viscosity within the above range, the content of the thickener is preferably 0.01 part by mass or more and 0.1 part by mass or less, and more preferably 0.02 part by mass or more and 0.08 part by mass or less, per 100 parts by mass of cement.

[0029] [Foaming material] The mortar material of the present embodiment preferably contains a foaming substance. The foaming substance is used for the purpose of more effectively preventing the mortar from sinking or shrinking due to bleeding when the mortar is not yet hardened after application. The foaming substance is preferably a gas foaming substance that generates gas after being mixed with water.

[0030] Examples of the gas foaming substance include oily substances such as vegetable oil and mineral oil. Examples of the gas foaming substance include powder substances such as flaky aluminum powder surface-treated with stearic acid or the like, and aluminum powder produced by an atomization method. Examples of the gas foaming substance include nitrogen gas foaming substances that foam nitrogen gas under an alkaline atmosphere, such as azo compounds, nitroso compounds, and hydrazine derivatives. Examples of the gas foaming substance include percarbonates such as sodium percarbonate, potassium percarbonate, and ammonium percarbonate, perborates such as sodium perborate and potassium perborate, permanganates such as sodium permanganate and potassium permanganate, and peroxides such as hydrogen peroxide.

[0031] As the gas foaming substance, it is preferable to use flaky aluminum powder that has been surface-treated with stearic acid or the like, because this has a large effect of suppressing sinking.

[0032] From the viewpoint of further suppressing bleeding, the content of the foaming substance in the mortar is preferably 0.0001 to 1%, more preferably 0.0005 to 0.5%, and even more preferably 0.001 to 0.2%.

[0033] [Water reducing agent] The mortar material of the present embodiment preferably contains a water reducing agent. The water reducer aids in the dispersion of each material and also serves to improve the fluidity of the mixed grout material.

[0034] The water reducing agent is not particularly limited, and examples thereof include naphthalene-based water reducing agents, melamine-based water reducing agents, aminosulfonic acid-based water reducing agents, and polycarboxylic acid-based water reducing agents, which can be used alone or in combination.

[0035] Specific examples of water reducing agents include naphthalene-based water reducing agents such as "Leobuild SP-9 Series" manufactured by NMB Corporation, "Mighty 2000 Series" manufactured by Kao Corporation, and "Sunflow HS-100" manufactured by Nippon Paper Industries Co., Ltd. Melamine-based water reducing agents such as "Sikament 1000 Series" manufactured by Sika Japan Co., Ltd. and "Sunflow HS-40" manufactured by Nippon Paper Industries Co., Ltd. Aminosulfonic acid-based water reducing agents such as "Paric FP-200 Series" manufactured by Fujisawa Pharmaceutical Co., Ltd. Polycarboxylic acid-based water reducing agents such as "Leobuild SP-8 Series" manufactured by NMB Corporation, "Darlex Super 100PHX" manufactured by Grace Chemicals Co., Ltd., and "Chupol HP-8 Series" and "Chupol HP-11 Series" manufactured by Takemoto Oil & Fat Co., Ltd.

[0036] Powdered water reducing agents are also available. Specifically, naphthalene-based water reducing agents include Kao Corporation's product name "Mighty 100", Sanyo Chemical Industries' product name "Sanyo Revlon P", and Daiichi Kogyo Seiyaku's product name "Cellflow 110P". Melamine-based water reducing agents include BASF Pozzolith's product name "Melment F10M". Polycarboxylic acid-based water reducing agents include Mitsubishi Chemical Corporation's product name "Queenflow 750" and Kao Corporation's product name "CAD9000P".

[0037] From the viewpoint of better fluidity, the content of the water reducing agent in the mortar is preferably 0.1 to 2% in terms of solid content, more preferably 0.2 to 1.8%, and even more preferably 0.3 to 1.0%.

[0038] In addition, the mortar material of this embodiment contains fine powder that has passed through a sieve with a mesh size of 90 μm, and contains TiO 2 It is preferable that the content of TiO is 0.03 mass % or more, more preferably 0.03 to 5 mass %, and further preferably 0.05 to 3 mass %. 2By containing 0.03 mass% or more of TiO, it is possible to impart thixotropy to the mortar, making it possible to prevent material separation while exhibiting good filling properties. 2 To contain 0.03 mass% or more of TiO 2 A material containing the above (for example, titanium oxide) may be used. In addition, fine powders with a sieve size of 90 μm or less have a relatively high initial reactivity, so TiO 2 By containing a certain amount of TiO 2 It is presumed that this makes it easier for the function, i.e., the thixotropy, to be exhibited.

[0039] The mortar material of this embodiment is a fine powder that has passed through a sieve with an opening of 90 μm and contains the following chemical components: P 2 O 5 The content is preferably 0.05 to 5 mass %, and more preferably 0.08 to 3 mass %. 2 O 5 By setting the content of 0.05 to 5 mass %, it becomes easier to maintain fluidity and to suppress flow-down, etc. 2 O 5 To contain 0.05 to 5 mass%, the material should be P 2 O 5 A material containing the above (for example, calcium phosphate) may be used.

[0040] [Mortar manufacturing method] The mortar material of this embodiment is mixed with water to produce mortar. The mortar material may be produced by mixing the respective materials at the time of construction, or may be mixed partially or entirely in advance. The method of mixing the respective materials and water is not particularly limited, and the respective materials may be mixed at the time of construction, or may be mixed partially or entirely in advance. Also, a portion of the materials may be mixed with water, and then the remaining materials may be mixed.

[0041] As the mixing device, any existing device can be used, for example, a tilting mixer, an omni mixer, a Henschel mixer, a V-type mixer, a Nauta mixer, or the like.

[0042] The amount of water used for mixing is not particularly limited because it varies depending on the purpose and application of use and the content of each material, but is preferably 10 parts by mass or more and 200 parts by mass or less, more preferably 12 parts by mass or more and 150 parts by mass or less, and even more preferably 14 parts by mass or more and 100 parts by mass or less, relative to 100 parts by mass of the above-mentioned cement. By having the amount of water used for mixing be equal to or more than the above lower limit, the fluidity is improved and the workability is improved. In addition, by having the amount of water used for mixing be equal to or less than the above upper limit, it is easier to ensure strength development.

[0043] (Application) The mortar according to the present embodiment can be suitably used for plastering and the like as a base material, finishing material, repair material, joint material, and the like, and is particularly preferably used as a repair material. In particular, a repair material containing the mortar of the present embodiment is preferred. In this case, the mortar composition is preferably contained in an amount of 90 mass % or more, and more preferably 100 mass %.

[0044] When used as a repair material, examples of the repair target include hardened mortar or concrete parts that have deteriorated, been damaged, or been broken. Some repair areas are large, while others are small, and the repair method is selected based on the repair area and the amount of repair material applied. If the area is relatively large, spraying is often used. On the other hand, if the repair area is small, it is preferable to apply the repair material with a trowel. When performing partial cross-sectional repair, the area is small but the thickness of the repair material is often thick, so a method of applying multiple layers is used. EXAMPLES

[0045] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0046] (Materials used) Cement: Denka "ordinary cement" ·CaO raw material: limestone powder ·Al 2 O 3 Raw material: bauxite powder Fe 2 O 3 Ingredients: Iron oxide powder SiO 2 Raw material: silica powder TiO 2 Raw material: titanium dioxide powder P 2 O 5 Ingredients: Calcium phosphate powder Expansion material: Denka Power CSA Fine aggregate: crushed sand (derived from limestone) Thickener: Methylcellulose, commercially available Foaming material (gas foaming material): flaky aluminum powder with a surface treatment using stearic acid, commercially available Water reducing agent: Naphthalene-based water reducing agent, "Cellflow 110P" manufactured by Daiichi Kogyo Seiyaku Co., Ltd. Water: Tap water

[0047] <Experimental Example 1> (Mortar manufacturing) Mortar was produced by mixing cement, expansive agent, fine aggregate, and water in the ratios shown in Table 1. 1.0 part by mass of water reducing agent was mixed per 100 parts by mass of cement. 0.01 to 0.1 part by mass of thickener was mixed per 100 parts by mass of cement to obtain the vibration viscosity shown in Table 1.

[0048] Mortar was also prepared separately for vibration viscosity measurement. 100 parts by mass of mortar material was mixed with 18 parts by mass of water, and measurements were started within 5 minutes after mixing was completed. The vibration viscosity was measured 1 minute after the start of measurement using a tuning fork vibration viscometer SV-10 (manufactured by A&D Co., Ltd.).

[0049] The mortar thus produced was subjected to the following filling test to evaluate the void ratio and fluidity. The results are shown in Table 1.

[0050] <Filling rate of filling test> Mortar is poured into a box-shaped container 100cm long, 100cm wide, and 5cm high with a Φ4cm hole in the centre of each of two opposing sides through one of the holes. Pouring of the mortar is stopped when the mortar flows out of the other hole. After the mortar has hardened, the container is removed and the mortar filling rate is measured for the top 100cm x 100cm area. To measure the filling rate, a 100cm x 100cm vinyl sheet is prepared and affixed to the top of the hardened body, marking the unfilled areas. The marked areas are then cut away, and the weight of the vinyl with only the filled areas remaining is measured and calculated using the formula below. Filling rate (%) = weight of vinyl in filled area (g) / total weight of vinyl (g) A high filling rate is preferable.

[0051] <Liquidity> In accordance with JSCE-F541, the J14 funnel flow rate was measured in a 30°C environment immediately after mixing (immediately after preparing the mortar) and 30 minutes later. The fluidity immediately after mixing is preferably 6 to 10 seconds, and the fluidity after 30 minutes is preferably 20 seconds or less.

[0052] [Table 1]

[0053] As shown in Table 1, the vibration viscosity is 50 to 600 (mPa s g / cm 3 In Test Nos. 1-2 to 1-4, which are in the range of 1-2 to 1-4, good results were obtained in terms of the filling rate and fluidity. Vibration viscosity is 50 (mPa·s·g / cm 3 In test No. 1-1, the filling rate was not measurable and the fluidity was low. The vibration viscosity was 600 (mPa·s·g / cm 3 In Test No. 1-5, in which the filling rate exceeded 90%, the fluidity was poor.

[0054] <Experimental Example 2> Except for changing the fine aggregate fraction (FM) of the fine aggregate and the fine aggregate / (cement+expansive agent) ratio, mortar was produced in the same manner as in Experimental Example 1. The results are shown in Table 2.

[0055] [Table 2]

[0056] As shown in Table 2, Test Nos. 1-3 and 2-2-3, in which the fine aggregate coarse grain ratio (FM) was in the range of 1.2-2.2, showed high filling ratios and good fluidity. Test Nos. 1-3 and 2-7-8, in which the fine aggregate / (cement + expansive agent) ratio was in the range of 60-230%, also showed high filling ratios and good fluidity.

[0057] <Experimental Example 3> (Mortar manufacturing) CaO raw material, Al 2 O 3 Raw material, Fe 2 O 3 Raw material, SiO 2 Raw materials and TiO 2 Raw material, P 2 O 5 The raw materials were mixed so that the chemical components were in the proportions shown in Table 1, then calcined at 1,350°C to synthesize clinker, which was then milled in a ball mill to produce a Blaine specific surface area of ​​3,500 cm. 2 The cement was then crushed to 1.0 parts by mass / g to produce cement. The cement, expansive agent, fine aggregate, and water were mixed in the ratios shown in Table 3. 1.0 part by mass of water reducing agent was mixed per 100 parts by mass of cement.

[0058] The chemical composition of the prepared cement and the fine powder TiO that passed through a 90 μm mesh sieve were 2 , P 2 O 5 The content was measured. CaO, Al 2 O 3 , Fe 2 O 3 , SiO 2 The amount of TiO was measured by X-ray fluorescence diffraction (XRF).2 and P 2 O 5 The above were also measured by X-ray fluorescence diffraction (XRF). The "other" components in the table are SO 3 , MgO, Na 2 OK 2 It is a trace component such as O.

[0059] The vibration viscosity of the produced mortar material was measured. The void ratio and fluidity of the produced mortar were also evaluated in a filling test. The results are shown in Table 3.

[0060] [Table 3]

[0061] As shown in Table 3, TiO 2 By containing 0.03 mass % or more, the filling rate can be increased and the flowability is also good. 2 O 5 By including 0.05 to 5 mass %, it was possible to increase the filling rate and prevent the fluidity from decreasing.

[0062] (Experimental Example 4) Except for mixing a foaming substance when producing the mortar, the mortar was produced in the same manner as in Experimental Example 1. The results are shown in Table 4.

[0063] [Table 4]

[0064] As shown in Table 4, Test No. 4-1, which used a foaming agent, showed good results in terms of both filling rate and fluidity, similar to Test No. 1-3, which did not use a foaming agent. Also, although not shown in Table 4, Test No. 4-1 was able to prevent the unhardened mortar from settling and shrinking due to bleeding. [Industrial Applicability]

[0065] The mortar material of the present invention can be suitably used for plastering and the like, as a base material, a finishing material, a repair material, a joint material, and the like.

Claims

1. The vibration viscosity of the mortar immediately after mixing with a standard water ratio is measured with a vibration viscometer and is 50 to 600 (mPa·s·g / cm 3 ) and The standard water ratio is 18 parts by weight of water per 100 parts by weight of mortar material; Contains cement, expansive material, and fine aggregate, The expanding material contains 0.5 parts by mass or more and 20 parts by mass or less per 100 parts by mass of cement, The mass ratio of the fine aggregate to the mass of the binder is 60 to 230%, and the binder is the cement and the expansive material; A mortar material, in which fine powder passed through a sieve with 90 μm openings contains 0.03 mass % or more of TiO 2 as a chemical component.

2. The vibration viscosity of mortar immediately after mixing with a standard water ratio, measured with a vibration viscometer, is 50 to 600 (mPa·s·g / cm 3 ); The standard water ratio is 18 parts by weight of water per 100 parts by weight of mortar material; Contains cement, expansive material, and fine aggregate, The expanding material contains 0.5 parts by mass or more and 20 parts by mass or less per 100 parts by mass of cement, The mass ratio of the fine aggregate to the mass of the binder is 60 to 230%, and the binder is the cement and the expansive material; A mortar material, in which fine powder passed through a sieve with 90 μm openings contains 0.05 to 5 mass % of P 2 O 5 as a chemical component.

3. A mortar material as described in claim 1 or 2, wherein the coarse aggregate ratio of the fine aggregate is 1.2 to 2.

2.

4. 3. The mortar material according to claim 1 or 2, which contains a foaming agent.

5. A composition comprising a thickener, The mortar material according to claim 1 or 2, comprising 0.01 parts by mass or more and 0.1 parts by mass or less of the thickener per 100 parts by mass of cement.

Citation Information

Patent Citations

  • Preparation method of goaf filling slurry for mine

    CN107540303A

  • Anti-pulling type rigidity-controllable piled raft foundation structure and construction method

    CN113863349A

  • Agent for improving ground consolidation and suspension type grout agent and ground improvement using the same

    JP1999349941A

  • Premixed mortar

    JP2006056730A

  • Filler and post-application anchor process

    JP2014189461A